The effects of preparation and acoustic stimulation on contralateral and ipsilateral corticospinal excitability - Marinovic, Welber; Flannery, V.; Riek, S. (Elsevier BV; North Holland, 2015)
A loud auditory stimulus (LAS) presented together with an imperative stimulus during preparation for motor actions can speed their initiation. The effects of LAS on corticospinal excitability (CSE), however, depend on the state of preparation of the motor system for action. CSE also depends on the brain hemisphere controlling the responding limb. Usually, CSE is increased just before movement onset in the hemisphere controlling the movement and inhibited on the other side. This study investigated the impact of LAS on CSE of the contralateral and ipsilateral hemispheres, while participants prepared for a voluntary abduction of the index finger. In Experiment 1, we attempted to identify the pattern of modulation of the ipsilateral cortex (resting side) by determining the time course of corticospinal changes in anticipatory timing actions using transcranial magnetic stimulation. In Experiment 2, we investigated the impact of LAS on the ipsilateral and contralateral CSE during anticipatory preparation. Results found no modulation of ipsilateral CSE during preparation, but indicate an increase in CSE after EMG onset on the acting limb. Moreover, we found that LAS presentation increased CSE on the contralateral side (active side).